6 CD98 identifies a clinically relevant subpopulation of head and neck squamous cell carcinoma cells with stem cell properties. Issue 5 (May 2015) - Martens-de Kemp, S.R.; Rietbergen, M.M.; Brink, A.; Walsum, M. Stigter-van; Bloemena, E.; van Wieringen, W.N.; Slijper, M.; Braakhuis, B.J.M.; Leemans, C.R.; Brakenhoff, R.H.
<x xml:space="preserve">Abstract</x> Introduction Patients with advanced head and neck squamous cell carcinomas (HNSCC) are often treated with concomitant chemotherapy and radiotherapy, but only 50% is cured. A possible explanation for treatment failure is therapy resistance of the cancer stem cells (CSCs). The application of compounds specifically targeting these CSCs, in addition to routinely used therapeutics, would likely improve clinical outcome. We set out to identify the CSC population in HNSCC. Previously, we found that the antibody K984 specifically targets the cells composing the squamous basal cell layer, the area where HNSCC CSCs likely reside. Materials and methods Immunoprecipitation and mass spectrometry was used to identify the antigen targeted by the K984 antibody. Next, flow cytometry was used to separate cell populations with high and low K984 antigen expression and these populations were tested for tumorigenicity in immunodeficient mice. Gene expression arraying was applied to further characterize the cell populations. In addition, to investigate the clinical importance of CSC presence in HNSCC, a large cohort of oropharyngeal tumors was immunohistochemically examined for K984 antigen positivity, as well as for CD44 expression, and the scoring results were associated with clinical outcome. Results We demonstrated that the monoclonal antibody K984 recognizes the CD98 cell surface protein and showed that CD98high cells, in contrast to CD98low cells, are able to generate tumors in immunodeficient mice. This indicates that CD98high cells have stem cell characteristics. Furthermore, the CD98high subpopulation expressed high levels of cell cycle control and DNA repair genes, while the CD98low fraction showed expression patterns that represent the more differentiated cells that form the bulk of the tumor. HPV-positive tumors expressed lower levels of CSC markers CD44 and CD98 than HPV-negative tumors. The number of CD98-positive cells was significantly associated with outcome in HPV-positive tumors, but not in HPV-negative tumors. CD44 expression was not associated with clinical outcome. Conclusion CD98 is a promising CSC enrichment marker in HNSCC. Our data support the CSC concept in head and neck cancer and the potential relevance of these cells for treatment outcome.